Quality of Professional Psychologist Training in Online Space - Nalyvaiko, Oleksii; Lykhoshvai, Kseniia (Educational Challenges, 2021)
The article is devoted to the definition of the basic provisions of training psychologists in the conditions of forced distance learning. The purpose of the study is to analyze the main qualities that a future psychologist should have, and to consider the impact of online learning (forced distance learning) on their quality and formation. The main objectives include: analyze theoretical framework of modern training of a psychologist; analyze the role of digital and online technologies in teaching future psychologists; analyze the answers given by student psychologists during a survey aimed at determining the role of online learning; propose recommendations for improving the learning process of future psychologists in a distance / blended learning. Among the research methods used, the following methods of scientific research were defining: analysis and generalization of scientific and methodological sources, governmental documents on the topic of research for the theoretical substantiation of the research problem, modeling of the data obtained. The authors also conducted a survey. The results of the study show that based on the analysis of the answers received from psychology-students, we can draw several main conclusions: most students would prefer classroom or blended learning; main difficulties faced by students: technical / internet problems, motivation (self-organization), difficulties in communicating with teachers; a significant part of students do not have practical skills and relevant information on working in the online space. Based on the analysis of the obtained results and own experience of work and study at the School of Psychology, recommendations are provided for first-year students and teachers in online learning. In conclusion, in the context of improving the quality of training of future psychologists in distance and blended learning, we recommend implementing from the first semesters of study in university courses aimed at familiarizing students with the norms of behavior in the digital space.